Team building with limited resources - S. V. Petrov (Путеводитель предпринимателя, 2020)
The content of this article is focused on the study of team building technology. The basic system-forming signs of team building are considered, including in the field of application to team building in conditions of limited resources, ways to overcome the problems that arise when forming an effective team.